Community mobilization: a key to effective control of banana Xanthomonas wilt - Kubiriba, Jerome; Karamura, E.B.; Jogo, W.; Tushemereirwe, Wilberforce K.; Tinzaara, William (2012)
Banana xanthomonas wilt (BXW) remains a major threat to banana, an important food and income crop for 12 million poor small-holder farmers in Uganda. Although, BXW has been controlled to some extent in parts of South-western Uganda, it is still a big problem in banana growing areas of Central and Eastern Uganda. We hypothesized that differential success in BXW control is mainly due to approaches used in the BXW control. This paper therefore, evaluates stakeholder mobilization approaches used in promoting technologies for BXW control in Uganda between 2006 and 2009. Results showed that farmer field schools host communities had more farmers (33%) that had low or no BXW infection (<10 infected plants) as compared to smaller proportions (23.5%) of farmers from communities that were using community action or that were mobilised using the traditional approach (22.9%) to control BXW. There was higher BXW prevalence in communities that were using community action (68.8%) or were mobilised traditionally (66.3%) than in those that hosted farmer field schools (43.4%). Consequently, there was higher (53%) banana production recovery on farms that hosted farmer field schools than those that used other institutional approaches (22%). BXW was better controlled by farmers mobilised using farmers field schools than those mobilized through community or traditional approaches.